The development of virtual conceptual change laboratory (VCCLab) for conception reconstruction through lab virtual activity. Issue 1 (March 2021) - Putri, K L; Suhandi, A; Samsudin, A; Surtiana, Y
Abstract: The research aimed to get a valid and tested VCCLab model product complete with syntax and supportive materials. This research is encouraged by the need for a VCCLab model for remedial teaching oriented towards remediation of students' misconceptions through the mode of virtual laboratory activity. The research method used is research & development which consists of four stages, namely: Need Analysis, Product Development, Field Testing, and Product Revision. From the development research process, the VCCLab model product is produced with syntax consisting of five stages of lab activity. The results of expert judgement on the VCCLab model product indicate that the VCCLab model and supporting materials have a construct and content validity. The results of limited field testing indicate that the use of the VCCLab model in remedial teaching activities with the mode of virtual lab activity has high effectiveness in remediating students' misconceptions regarding the concept of parallel electric circuit. Another field testing result is that there is no gender bias in the use of the VCCLab model in the students' conception reconstruction process related to the physics concept being reviewed.